Application of Sharī‘ah contracts in contemporary Islamic finance: a maqāṣid perspective - Soualhi, Younes (IIUM Press, 2015)
This research exposes the underlying maqāṣid embedded in Sharī‘ah contracts as applied in Islamic banking and finance. It addresses the problem of not observing maqāṣid in nominated and combined Sharī‘ah contracts as well as the problem of not sufficiently imbuing maqāṣid in products developed by Islamic financial institutions. As a benchmark of the maqāṣid of wealth, the research adopts Ibn ‘Āshūr’s classification of maqāṣid to evaluate the conformity of Sharī‘ah contracts to Maqāṣid al-Sharī‘ah namely, justice, circulation, transparency, and firmness. The study focuses on three markets related to the application of Sharī‘ah contracts, namely, banking, Islamic capital market, and takāful. The study concludes that, by and large, the application of Sharī‘ah contracts has observed Maqāṣid al-Sharī‘ah during its development and initial application stages of Islamic finance products; however, offering such products in the market has raised economic questions as to their viability and economic values. In addition, the malpractice of some Sharī‘ah contracts has long raised concerns as to the maqāṣid compliance of such products. The research recommends a de-sophistication of Islamic financial engineering to minimise the possibility of convergence with conventional finance. The research also emphasises product differentiation based on less complicated combined Sharī‘ah contracts.